New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India - David, K. J.; Hancock, D. L.; Singh, Shakti Kumar; Ramani, S.; Behere, G. T.; Salini, S. (Zootaxa, 2017)
Two new species of genus Bactrocera Macquart, namely B. (Sinodacus) brevipunctata David and Hancock, sp. nov. and B. (Bactrocera) furcata David and Hancock, sp. nov., are described from India. B. (B.) aethriobasis Hardy, B. (B.) rubigina Wang & Zhao, B. (B.) syzygii Tsuruta & White and B. (B.) tuberculata (Bezzi) are recorded for the first time from India. Updated keys to twelve subgenera of Bactrocera and Indian species of Bactrocera (Bactrocera) are also provided.